2018
DOI: 10.1111/mcn.12642
|View full text |Cite
|
Sign up to set email alerts
|

Severe malnutrition in infants aged <6 months—Outcomes and risk factors in Bangladesh: A prospective cohort study

Abstract: Severe acute malnutrition (SAM) affects ~4 million infants under 6 months (u6m) worldwide, but evidence underpinning their care is "very low" quality. To inform future research and policy, the objectives of our study were to identify risk factors for infant u6m SAM and describe the clinical and anthropometric outcomes of treatment with current management strategies. We conducted a prospective cohort study in infants u6m in Barisal district, Bangladesh. One group of 77 infants had SAM (weight-for-length Z-score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
(30 reference statements)
2
12
0
Order By: Relevance
“…The results are inconsistent, and the quality of studies varied. Several studies were conducted to examine associations between WASH conditions and acute malnutrition and the effect of WASH interventions on preventing this condition; however, results are mixed, and the evidence relies mostly on low‐ to moderate‐quality observational studies (Ambadekar & Zodpey, 2017 ; Ayana et al, 2015 ; Buttenheim, 2008 ; Chisti et al, 2007 ; Dodos et al, 2018 ; Fikree et al, 2000 ; George et al, 2016 ; Iannotti et al, 2009 ; Langford et al, 2011 ; Lin et al, 2013 ; Munirul Islam et al, 2018 ; Nabwera et al, 2018 ; Stobaugh et al, 2018 ; Tomedi et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results are inconsistent, and the quality of studies varied. Several studies were conducted to examine associations between WASH conditions and acute malnutrition and the effect of WASH interventions on preventing this condition; however, results are mixed, and the evidence relies mostly on low‐ to moderate‐quality observational studies (Ambadekar & Zodpey, 2017 ; Ayana et al, 2015 ; Buttenheim, 2008 ; Chisti et al, 2007 ; Dodos et al, 2018 ; Fikree et al, 2000 ; George et al, 2016 ; Iannotti et al, 2009 ; Langford et al, 2011 ; Lin et al, 2013 ; Munirul Islam et al, 2018 ; Nabwera et al, 2018 ; Stobaugh et al, 2018 ; Tomedi et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two high‐quality studies (du Preez et al, 2011 ; Stobaugh et al, 2018 ) and six low‐quality studies (Arnold et al, 2009 ; Dodos et al, 2018 ; Fikree et al, 2000 ; George et al, 2016 ; Lin et al, 2013 ; Munirul Islam et al, 2018 ) consistently demonstrated no association between measured water quality and prevention of acute malnutrition or improved WHZ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides shorter-term risks of death and morbidity, there are important long-term consequences for neurodevelopment and adult non-communicable disease ( Tarry-Adkins & Ozanne, 2011 ). The determinants of severe malnutrition in infants U6M are only just beginning to be studied ( Munirul Islam et al, 2018 ). It is not yet clear what proportion of infants are presenting with acute wasting as opposed to following a trajectory from LBW, whether premature or small for gestational age (SGA), and whether this has implications for assessment and treatment.…”
Section: Introductionmentioning
confidence: 99%